If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18t + -48 = 2 + 14t Reorder the terms: -48 + 18t = 2 + 14t Solving -48 + 18t = 2 + 14t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-14t' to each side of the equation. -48 + 18t + -14t = 2 + 14t + -14t Combine like terms: 18t + -14t = 4t -48 + 4t = 2 + 14t + -14t Combine like terms: 14t + -14t = 0 -48 + 4t = 2 + 0 -48 + 4t = 2 Add '48' to each side of the equation. -48 + 48 + 4t = 2 + 48 Combine like terms: -48 + 48 = 0 0 + 4t = 2 + 48 4t = 2 + 48 Combine like terms: 2 + 48 = 50 4t = 50 Divide each side by '4'. t = 12.5 Simplifying t = 12.5
| .44x=.27 | | 0.25-0.5x= | | 6(4-c)=5(c-2) | | 3(y-1)-(3y-1)=2y-1-(2y+1) | | 4x+-21x=91 | | x+5/3=2x-5/6 | | f(x)=x^3-7x^2+7x+15 | | w+(2w-4)+w+(2w-4)=46 | | 0.25-0.5=0.05 | | 7x^2-42=35x | | 3t+9=33 | | 9-9=12x+11x | | 8.2x-5=0 | | .50x+.4x=18 | | -60+2.5x=0 | | 16+t=-182 | | 15-4x=7-5x | | .10x+.25(x+4)+.05*5(x+4)=3.20 | | x+2y=zforx | | 3+4x+2x=12+4x-3x | | 4(1+6m)-8=-124 | | 3x+45=8x-220 | | 36=-9t | | 0=12m | | 21x^2+2x-.09=0 | | cos(x)=-05 | | (2xy)(3x^2y)= | | -84x^2+91x-7=0 | | 4y=8+3x | | (x^2-5)(5x)(-.25)= | | (n-2)180=108n | | 7(14a+7w)8(7a+9w)= |